2011
DOI: 10.1007/s00167-011-1582-1
|View full text |Cite
|
Sign up to set email alerts
|

Aperture fixation instead of transverse tunnels at the patella for medial patellofemoral ligament reconstruction

Abstract: Aperture fixation techniques, especially interference screw fixation, were as strong as the technique utilizing tunnels in the patella for MPFL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
62
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 23 publications
1
62
1
Order By: Relevance
“…While some studies have observed increased rates of postoperative patellar fracture after the use of bone tunnels for graft fixation, there has been a trend toward techniques that avoid utilization of tunnels. 15,35 Finally, our analysis also found that postoperative infections requiring surgical intervention are a rare (1.2%) complication after patellar instability surgery, which is consistent with previous studies. 33,38,49 …”
Section: Discussionsupporting
confidence: 92%
“…While some studies have observed increased rates of postoperative patellar fracture after the use of bone tunnels for graft fixation, there has been a trend toward techniques that avoid utilization of tunnels. 15,35 Finally, our analysis also found that postoperative infections requiring surgical intervention are a rare (1.2%) complication after patellar instability surgery, which is consistent with previous studies. 33,38,49 …”
Section: Discussionsupporting
confidence: 92%
“…Even in the study of Hapa et al 17 there have been no differences between the two techniques. However, there was a MPFL lower stiffness in the suture anchor group with respect to the bone tunnel group.…”
Section: Discussionmentioning
confidence: 84%
“…With the double-over semitendinosus graft yielding a tensile strength of approximately 2300 N and a stiffness of approximately 470 N/mm [36], the limiting factor in the construct is clearly the fixation. The 3.5-mm metal anchor used in this technique was found to have a pull-out strength of 295 N in a porcine model [37], in comparison, the pull-out strength of interference screw fixation in the setting of MPFL reconstruction have yielded slightly inferior results, with through-tunnel fixation failing at 195 N and aperture fixation failing at between 126 and 241 N [35,38]. Second, patellar fractures, the most serious complication after double-bundled MPFL reconstruction, have been reported only in procedures with patellar-bone tunnel fixation [24,28,29,39], for bone tunnels may act as stress risers whereas suture anchor fixation, sparing of bone drilling, such complication may be minimised.…”
Section: Discussionmentioning
confidence: 92%